The Impact of Womens Role in Corporate Governance on Carbon Disclosure Performance: A Descriptive Study of Top 100 Global Energy Leaders - Majid N.A.; Jaaffar A.H.; Alzoubi R.H.M. (Econjournals, 2024)
Global leaders in the energy sector have significantly improved their environmental governance practices by incorporating women into their management teams to enhance carbon reporting practices. Based on a content analysis of annual reports, sustainability reports, and websites of the top 100 global energy leaders, we describe the trend of women of the board member who are industry experts, act as advisors, and pose as community leaders as well as the level of their carbon disclosure (CD) performances over the 3 years from 2018 to 2020. The results show that the number of women on the boards of the top global energy leaders is increasing in line with the level of carbon disclosure over 3 years. This development exemplifies the significance of women in leadership roles in the top global energy leaders journey to achieve net zero carbon emissions. Women in managerial positions are therefore crucial, and their presence will be one of the most critical influences in the energy sectors potential to enhance firm carbon performance and draw in more sustainable economic growth. 2023, Econjournals. All rights reserved.